Synthesis, Optical and Electrochemical Properties of Two Series Electron-Donor Polymers with Diphenylpyranylidene Side Chain. (June 2020) - Tian, Wen-Ting; Bolag, Altan; Bao, Tana; Ning, Jun; Alata, Hexig; Ojiyed, Tegus
Abstract: Two series of novel conjugated polymers with diphenylpyranylidene as the side chain and thiophene as the main chain were designed, synthesized and characterized as electron donors of polymer solar cells for the first time. The absorption spectra showed that introduction of diphenylpyranylidene side chain can obviously complement the light absorption ability in the range from 300-500 nm. In addition, diphenylpyranylidene unit is also helpful to tune the HOMO energy level as low as -5.23 to -5.31 eV than P3HT polymers, for favoring higher open-circuit voltage in polymer solar cells.